x+23+3x=-20-3x-27

Simple and best practice solution for x+23+3x=-20-3x-27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+23+3x=-20-3x-27 equation:


Simplifying
x + 23 + 3x = -20 + -3x + -27

Reorder the terms:
23 + x + 3x = -20 + -3x + -27

Combine like terms: x + 3x = 4x
23 + 4x = -20 + -3x + -27

Reorder the terms:
23 + 4x = -20 + -27 + -3x

Combine like terms: -20 + -27 = -47
23 + 4x = -47 + -3x

Solving
23 + 4x = -47 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
23 + 4x + 3x = -47 + -3x + 3x

Combine like terms: 4x + 3x = 7x
23 + 7x = -47 + -3x + 3x

Combine like terms: -3x + 3x = 0
23 + 7x = -47 + 0
23 + 7x = -47

Add '-23' to each side of the equation.
23 + -23 + 7x = -47 + -23

Combine like terms: 23 + -23 = 0
0 + 7x = -47 + -23
7x = -47 + -23

Combine like terms: -47 + -23 = -70
7x = -70

Divide each side by '7'.
x = -10

Simplifying
x = -10

See similar equations:

| 92-4x=14x+22 | | 9x^2=21x | | 2x+20=4x+6 | | x(3x-2)(x+6)= | | (3s-2)(4s+4)= | | 7x+32=x^2+4 | | 3.42/34.2 | | 3.42/24.2 | | 12=x/11 | | 8c*3v= | | -36x^2+96x-36=0 | | 2(5x+3)=4x-10 | | 1/6=6x | | 20x=460 | | 6=-3/5(4)+b | | 6=-3/5(4) | | -2x-6y=-74 | | 8x+3=6x+33 | | x+x+8+2x=240 | | 6x-(4x+3)=7 | | 6.3x=18.9 | | 9t^3+15t^2+t-6=t^2+t-6-3t^3 | | -12x^3+48x^2-36x=0 | | 8x+47=8(x+4) | | 7(4x-9)=40 | | 3x+6=-5-1x | | 3x^3+4x^4-6x^5-9x^6+14x^7-6x^8+x^9=0 | | ((a^4)/(2a^2-4a^4))*((8a^3+1)/(2a+4a^2)) | | 7(3x-9)=34 | | x-15=31 | | 5(7x-9)=20 | | 14-3x=-16 |

Equations solver categories